Transformation of Taiwan's Upper Secondary Education System - Laih, Hueih-Lirng; Westbury, Ian (Education Policy Analysis Archives, 1998)
This paper explores the policy issues circling around the structural "transition" in upper secondary education implicit in the twenty-year increase in secondary and third-level school enrollment rates in Taiwan. This expansion has taken place within a secondary school system which is rigidly divided into both general, i.e., academic, and vocational tracks and into public and private sectors: the majority of students are enrolled in the private vocational sector which is only loosely articulated with the university sector. These features of the school system are analysed against the background of social and economic developments in Taiwan as well as public opinion. The analysis suggests that the present structures of school must be "reformed" in ways that will result in a more unified secondary system with both greater public funding and better articulation of all school types with the third level. The policy options that circle around the possibility of such reforms in the areas of curriculum, examination structures and second level-third level articulation are discussed and a policy framework for the reform of the Taiwan secondary education sector is outlined.